Costa Rican Orchidaceae types (CROTYPES) digital imaging documentation at AMES, Harvard University - Pupulin, Franco; Romero-González, Gustavo A. (Lankesteriana: International Journal on Orchidology, 2016)
Botanical collections in developed countries are not always restricted to their native plants. Many herbaria in those countries also host large collections from tropical and subtropical floras as the result of floristic projects carried out by leading European and North American botanical institutions in the past three cen- turies